Livestock sector investment and policy toolkit (LSIPT): Making responsible decisions - Food and Agriculture Organization of the United Nations; Centre de coopération internationale en recherche agronomique pour le développement; International Livestock Research Institute (Food and Agriculture Organization of the United Nations, 2020)
The Food and Agriculture Organization of the United Nations (FAO), together with the World Bank, the International Livestock Research Institute (ILRI) and the French Agricultural Research Centre for International Development (CIRAD), have developed the Livestock Sector Investment and Policy Toolkit (LSIPT) toolkit to support teams and decision-makers to increase and improve policies and livestock investments that contribute to achieving the Sustainable Development Goals. The toolkit enables a shift from the traditional approach centred on livestock production to one that focuses on households and human well-being with the goal of poverty reduction.